2012
DOI: 10.4236/ce.2012.38b016
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ ICT Skills and ICT Integration in the Classroom: The Case of Vocational and Technical Teachers in Malaysia

Abstract: This study was to determine the levels of ICT skills and ICT usage in the classroom among technical and vocational teachers in Malaysia. The data of this study were collected using quantitative techniques, whereby the questionnaire was administered to 329 technical and vocational teachers who were teaching engineering subjects in Malaysian technical and vocational schools. The questionnaire included items related to teachers' ICT skills, ICT use and their demographic factors. The study has shown that teachers'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
34
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 12 publications
12
34
0
1
Order By: Relevance
“…These results are in agreement with those of a few studies, such as those by Alazam et al (2012), Summak and Samancıoğlu (2011), and Jimoyiannis and Komis (2007), which all noted a significant difference in the teacher's extent of ICT skills in the classroom. Male teachers had higher mean scores in almost all of the items on basic competence, however, Aremu and Fasan (2011) found that females possessed higher computer selfefficacy than their male counterparts.…”
Section: Difference In the Information And Communication Technology (supporting
confidence: 92%
See 2 more Smart Citations
“…These results are in agreement with those of a few studies, such as those by Alazam et al (2012), Summak and Samancıoğlu (2011), and Jimoyiannis and Komis (2007), which all noted a significant difference in the teacher's extent of ICT skills in the classroom. Male teachers had higher mean scores in almost all of the items on basic competence, however, Aremu and Fasan (2011) found that females possessed higher computer selfefficacy than their male counterparts.…”
Section: Difference In the Information And Communication Technology (supporting
confidence: 92%
“…These findings are congruent with the results of Alazam et al (2012), Lau and Sim (2008), and Robinson (2003) wherein younger teachers had higher ICT skills than the older ones. In the study of Yu, Wang, and Lin (2013), the lower age groups (20-25 years old) differed significantly from the higher age groups, with the lower age groups indicating that they felt more competent in using software in teaching.…”
Section: Difference In the Information And Communication Technology (supporting
confidence: 90%
See 1 more Smart Citation
“…Teacher-centered learning would cause pupils to easily get bored and pupils will associates mathematics with negative perception. However, based on previous research, T&L using dynamic mathematical software attract pupils' attraction and motivation [10], [11], [12]. Researcher also found the use of GeoGebra in T&L showed positive effects to pupils in term of perception [13], [14] and motivation [15], [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…Good learning material should enhance not only pupils' achievement but also pupils' motivation [19]. By using ICT, it can increase pupils' motivation to learn, easy to understand and provide better opportunities for exercises and enrichment activities [10]. A good learning material should have four characteristics which are (1) the knowledge acquired by the pupils formed by mapping the actions and thoughts of pupils; (2) social interaction between pupils in order to develop knowledge [13], (3) knowledge formed is the result of activities undertaken by the pupils themselves and (4) communication between teachers is not the source of the knowledge of pupils rather only as a guide for pupils to develop cognitive schemes [8].…”
Section: Introductionmentioning
confidence: 99%